Evaluation of Intraligamentous and Intraosseous Computer-Controlled Anesthetic Delivery Systems in Pediatric Dentistry: A Randomized Controlled Trial - Andrea Prol Castelo; Eliane García Mato; Iván Varela Aneiros; Lucía Sande López; Mercedes Outumuro Rial; María Teresa Abeleira Pazos; Berta Rivas Mundiña; Jacobo Limeres Posse (MDPI AG, 2022)
Computer-controlled local anesthetic delivery systems (CDS) represent one of the resources that have progressed the most in recent years, but their efficacy and applicability in pediatric dentistry is still the subject of certain controversies. This randomized, controlled, split-mouth clinical trial assessed two CDS in children (n = 100) with deep caries in the temporary dentition that required invasive therapeutic procedures, using inferior alveolar nerve block as the gold standard. Half of the patients (n = 50) underwent the intraligamentary technique (Wand STA®) on one side of the mouth and conventional inferior alveolar nerve block on the contralateral side, while the other half (n = 50) underwent the intraosseous technique (QuickSleeper®) on one side of the mouth and conventional inferior alveolar nerve block on the contralateral side. The following were considered covariates: age, sex, type of dental procedure and the applied local anesthesia system. The outcome variables were the pain caused by the anesthesia injection, the physical reaction during the anesthesia injection, the need for anesthetic reinforcement, pain during the therapeutic procedure, the overall behavior during the visit, the postoperative morbidity and, lastly, the patient's preference. In conclusion, we confirmed the efficacy of intraligamentary and intraosseous techniques administered using a CDS for conducting invasive dental treatments in children, their advantages compared with inferior alveolar nerve block in terms of less pain generated by the anesthesia injection and less postoperative morbidity, as well as the pediatric patients' preference for CDS versus conventional techniques.